Research on mobility handover for IPv6‐based MANET. Issue 7 (30th October 2012) - Xiaonan, Wang; Shan, Zhong
ABSTRACT The paper proposes a mobility handover scheme for IPv6‐based mobile ad hoc network (MANET) Mobility Handover (IMMH). In IMMH, when a node moves out of the communication scope of its upstream node, it is the node that directly establishes the routing path reaching to the upstream node in the Unicast way, which reduces the mobility handover cost and shortens the mobility handover delay. In mobile ad‐hoc networks without any infrastructures, a user always uses a node's home address to communicate with the node, and both the node's mobility handover process and its care‐of address update process are transparent to the user. Therefore, the communication continuity is ensured. From both the theoretical perspective and the simulative perspective, the paper analyzes the performance parameters of IMMH, including the mobility handover cost and the mobility handover delay. The data results show that the mobility handover cost of IMMH is lower and the delay is shorter.Copyright © 2012 John Wiley & Sons, Ltd.